Short-term impacts of operational fuel treatments on modelled fire behaviour and effects in seasonally dry forests of British Columbia, Canada - Rutherford, Kea H.; Eskelson, Bianca N. I.; Daniels, Lori D.; LeMay, Valerie; Greene, Gregory A.; Gray, Robert W. (International journal of wildland fire, 2025)
BackgroundIn response to increasing risk of extreme wildfire across western North America, forest managers are proactively implementing fuel treatments.AimsWe assessed the efficacy of alternative combinations of thinning, pruning and residue fuel management to mitigate potential fire behaviour and effects in seasonally dry forests of interior British Columbia, Canada.MethodsAcross five community forests, we measured stand attributes before and after fuel treatments in 2021 and 2022, then modelled fire behaviour and effects using the Fire and Fuels Extension to the Forest Vegetation Simulator.Key resultsFor our study area, field measurements combined with fire behaviour modelling indicated: (1) low-intensity thinning from below reduced potential of passive crown fire, whereas high-intensity thinning reduced potential of passive and active crown fire; (2) pruning after thinning from below did not further reduce potential of passive crown fire; and (3) chipping or pile burning of residue fuel mitigated potential of passive crown fire, but fire effects associated with chipping remain a concern.Conclusions and implicationsThere is limited prior research on the impacts of fuel treatments in western Canada. This research contributes to better understanding the potential impacts of fuel treatments in the fire-prone forests of interior British Columbia.